Implementasi Pendekatan Saintifik Dalam Meningkatkan Pengenalan Tanaman Pada Anak-Anak Kelompok A Di TK Yudistira Kumara II Sembung Kecamatan Mengwi Kabupaten Badung - Purwayanti, Ni Made Dwi; Sudarsana, I Ketut; Budiasih, Ni Wayan (Jayapangus Press, 2021)
Early childhood is a sensitive period or golden age, where there is rapid development so that teachers must be smart in choosing a learning approach so that learning objectives can be achieved properly, one of which is a scientific approach. The implementation of the scientific approach is intended to provide understanding to students in recognizing, understanding various materials using a scientific approach, that information can come from anywhere, not depending on unidirectional information from the teacher. Scientific learning teaches children to find new knowledge, solve problems, think critically and create creativity so that it helps them understand the environment, especially plants, collect and process information as the basic keys for children to think broadly. Therefore the expected learning conditions are directed to encourage students to find out from various sources through observation, and not just being told. The theory used to analyze the problem is Piaget's theory of cognitivism. This research is a classroom action research with the method of documentation, observation and interviews from the implementation of the cycle, the observation method is carried out using an observation format which includes three indicators including, indicator I: mentioning the kinds of plants, indicator II: counting and classifying the kinds of plants according to type III indicator: distinguishing parts, types and forms of plants and mentioning the color of the plant. The results of the observations obtained from the learning outcomes in each cycle were analyzed quantitatively with descriptive statistics using the percentage technique. The subjects of this research were the children of group A TK Yudistira Kumara II Sembung. The results showed that with a scientific approach it could improve the ability to recognize plants in group A in TK Yudistira Kumara II Sembung. The percentage of the initial state, cycle I and cycle II shows an increase. The results of research on the implementation of the scientific approach in improving plant recognition were resolved in Cycle II and the research was successful